Mental retardation - Bierne-Smith, Mary.; Ittenbach, Richard; Patton, James R. (Upper Saddle River, N.J. : Merrill, 1998)
Provides educators with information about the many facets of mental retardation from a life cycle perspective. This introductory text focuses on the basic concepts about mental retardation, the characteristics of individuals who have different levels of retardation, programming and issues across the lifespan of individuals who are retarded.
Includes bibliographical references and indexes.
Keywords: Intellectual disability